CORPORATE IMAGE AND SERVICE QUALITY PERCEPTION ON CUSTOMER’S TRUST AND ITS IMPACT TO THEIR INTEREST IN BEING CUSTOMER - Komarudin, Munir Nur; Hurriyati, Ratih; Manalu, Vigory Gloriman; Yunior, Ray (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
This research having the purpose of establishing a model that will be used to understand, analyze, and test the gap of about variables corporate image owned by PD BPR Balongan Cirebon on purchase intention to be customer on Cirebon community, so that this research aims to build a model new for marketing in the banking sector. Analysis tool used in this study is SEM (Structural Equation Modelling). The result of the study shows there are significant effect between corporate image and trust, perception of service quality and trust, corporate image and purchase intention, trust and purchase intention, and perception of service quality and purchase intention. Keywords: Corporate Image, Perception of Service Quality, Trust, Purchase Intention